THE INFLUENCE OF EMPLOYER BRANDING, WORK EXPECTATIONS, AND CORPORATE REPUTATION ON INTENTION TO APPLY FOR A JOB AMONG FINAL-YEAR MANAGEMENT STUDENTS AT THE FACULTY OF ECONOMICS AND BUSINESS, UNIVERSITAS MALIKUSSALEH - Shadaqta Amalia; Khairawati; A Hadi Arifin; Sullaida (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
The purpose of this study is to analyze the influence of employer branding, work expectations, and corporate reputation on Intention to Apply for a Job among final-year students in the Management Study Program, Faculty of Economics and Business, Malikussaleh University. The study was conducted on final-year students in the 2022 intake of the Management Study Program, Faculty of Economics and Business, Malikussaleh University. The research method used a quantitative approach, distributing questionnaires to 175 final-year student respondents. Data analysis was performed using the Partial Least Squares (PLS) method with the assistance of the SmartPLS application. The results showed that employer branding had a positive and significant effect on Intention to Apply for a Job, work expectations had a positive and significant effect on job application intentions, and corporate reputation had a positive and significant effect on Intention to Apply for a Job. These findings indicate that employer branding, work expectations, and corporate reputation are important factors that can encourage increased Intention to Apply for a Job, particularly in the decision-making process of applying to a company.